Counseling as a Strategic Intervention for Mitigating the Consequences of Marital Dissolution among Secondary School Teachers - Jamila YUSUF; Mustapha Shina Ahmed; Habeebah Bolanle YAHYA-ABDULKAREEM; Habibat Bolanle ABDULKAREEM (Universitas Pendidikan Ganesha, 2025)
Marital dissolution among secondary school teachers is a growing concern with far-reaching emotional, social, and professional consequences. The demands of the teaching profession, coupled with financial pressures and work-life conflicts, often contribute to relationship breakdowns, leaving affected teachers vulnerable to stress, stigma, and decreased job performance. This paper explores the impact of marital dissolution on teachers. The study adopted a descriptive survey design with a quantitative approach. The research instrument consisted of a structured questionnaire divided into several sections: demographic information, stressful life events, coping resources, personal perceptions, and adaptation outcomes. Data analysis was conducted using both descriptive and inferential statistical techniques. The result found counseling provides emotional support, stress management techniques, problem-solving skills, and referrals to essential resources such as legal aid and financial advisors. Addressing marital dissolution through targeted counseling interventions will not only enhance teachers' well-being but also improve their overall effectiveness in the classroom. It is therefore suggested that teachers should prioritize communication in their marriage. Open and honest communication is key to a healthy marriage. Teachers should set aside time to discuss feelings, resolve conflicts early, and actively listen to their partners. Clear communication strengthens emotional bonds and prevents misunderstandings that can lead to marital breakdown.